Stress Coping Styles and Academic Achievement: A Correlational Study - Syeda Omaima Mehak; Ayla Khan (Social Science Review Archives, 2026)
Stress is a fundamental component of student life and has significant effects on the academic achievement of learners. The present research study attempted to find out the correlation between ways to cope with stress and academic achievement in university students. The correlational research approach was applied to gather information regarding a group of 500 learners who were participating in three different governmental universities: the University of Haripur, Abbottabad University of Science and Technology, and Hazara University in Mansehra, Pakistan. Respondents represent a broad spectrum of academic disciplines and program levels. The stress coping techniques were evaluated using standard methods, including problem-focused coping, emotion-focused coping, avoidant coping, and social support coping, while academic achievement was gauged through self-reported GPA. Pearson product-moment correlation analysis revealed a relatively favourable link between problem-focused coping and academic achievement (r =.42, p <.01) showing that it indicates learners who effectively manage stresses seem to succeed better academically. Dealing with peer support has been associated to greater educational achievement (r =.30, p <.01). Emotion-focused coping (r = -.28, p <.01) and avoidant coping (r = -.35, p <.01) exhibited substantial negative correlations with academic performance. Interrelationships between coping styles demonstrated that appropriate coping methods had a positive relationship to academic success, although maladaptive strategies were inversely related. The findings highlight the importance of supportive adaptive coping techniques to improve students' academic achievement and psychological well-being. The implications for counselling services and stress management therapies in university settings are explored.